Twenty-two years of advancements in augmented and virtual reality: a bibliometric and systematic review - Angra, Sheena; Jangra, Shinnu; Gulzar, Yonis; Sharma, Bhanu; Singh, Gurjinder; Onn, Choo Wou (Frontiers in Computer Science, 2025)
PurposeThe study aimed to investigate the utilization of immersive technologies, such as augmented reality (AR) and virtual reality (VR), in various domains, with a particular focus on the teaching–learning process. In addition, the study sought to conduct a bibliometric analysis of relevant articles indexed in the SCOPUS database.MethodsA comprehensive search was conducted to identify papers related to AR and VR. Subsequently, a bibliometric analysis was carried out using articles retrieved from the SCOPUS database. In addition, a systematic literature review (SLR) was undertaken to elucidate the application of immersive technologies across diverse fields, such as machine learning (ML), Internet of Things (IoT), and artificial intelligence (AI).ResultsThe findings indicated a gradual consolidation of studies on immersive technologies over the past two decades, with a notable turning point around 2015. The analysis identified the United States as the most influential country in this domain. However, despite advancements, research specific to AR and VR is still in the early stages, suggesting the necessity for further investigation to achieve a comprehensive understanding and utilization of these technologies. The SLR provided insights into the integration of immersive technologies across various disciplines, highlighting their potential applications beyond the teaching–learning context.ConclusionWhile immersive technologies have demonstrated significant potential in enhancing learning experiences, their widespread adoption and utilization across different sectors remain in nascent stages. The study investigates key technological effects, global research collaborations, and developing themes to determine critical trends and knowledge gaps. The findings suggest insights into how AR/VR research has grown in response to user needs and technological innovations, providing a roadmap for future analyses. The study underscores the importance of continued research efforts to explore the full capabilities of AR and VR and their integration with emerging technologies such as machine learning and artificial intelligence.